Marketing Communication Strategy on Instagram Social Media @ninetynine.indo in Increase Brand Awareness - Yoga Permana Putra; Eka Anisa Sari (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2024)
This study aims to discover Ninetynine's marketing communication strategy for increasing Brand Awareness through Instagram social media @ninetynine.imdo. This study uses a qualitative research method with a Descriptive approach. The data collection techniques used in interviews, observations, and documentation were processed and analyzed using marketing mix theory and persuasion knowledge theory. The study results show that Ninetynine's marketing communication strategy has succeeded in increasing brand awareness on Instagram, with one of them optimizing Instagram features, most of which have been done well. The marketing strategy to increase Brand Awareness so that it continues to exist, Ninetynine still has to promote and improve so that its products continue to grow and become more expansive and remain in demand by Consumers, which is by the 7P Marketing Mix by Kotler and Keller, namely: 1) Product. 2) Price. 3) Place. 4) Promotion by implementing a promotion mix such as Advertising, Sales promotion, Direct marketing, Public relations, and Internet marketing. 5) People (participants/people). 6) Process. 7) Physical evidence.